Website accessibility of travel agents: an evaluation using web diagnostic tools - Eusébio, Celeste (2022)
Travel agents (TA) play an important role in the tourism system, providing information and intermediating the purchase of tourism products. The relevance of these players is higher to the accessible tourism market, due to the various environmental, attitudinal and informational constraints that people with disabilities (PwD) face in carrying out a tourism trip. To overcome some of the information constraints, communication channels, such as websites, used by TA, should be accessible for all people, regardless of their psychological and physical abilities. To accomplish this aim, in this study the website accessibility of (TA) located in the Central Region of Portugal was examined. Based on the Web Content Accessibility Guidelines (WCAG) 2.0, a sample of 182 websites was analyzed, considering the three-conformance level of WCAG (A, AA and AAA) and using two automatic evaluation tools (AccessMonitor and “Test de Accesibilidade Web”—TAW). Results show that the websites of TA reveal several problems in relation to accessibility, particularly in the basic accessibility requirements (level A of the WCAG). Moreover, several problems were identified, mainly in the perceivable and robust principals. The paper ends with some guidelines to increase the level of web accessibility of TA.